Erythema Multiforme Attributable to Herpes Simplex Virus: Clinical Aspects and Treatment - Aya Mtiri; Ghada Bouslama; Nour-sayda Ben Messouad; Iyadh Abidi; Souha Ben Youssef; Badreddine Sriha (Hindawi Limited, 2021)
Erythema multiforme is an acute mucocutaneous hypersensitivity reaction with various etiological factors, including herpes simplex virus, medications, autoimmune diseases, and malignancies, but the most common cause is infection by herpes simplex virus. The most characteristic feature is the presence of "target lesions." There are no specific diagnostic tests for EM, and the diagnosis is based on clinical signs and symptoms and biopsy if required. We report a case of recurrent herpes-associated erythema multiforme managed with prophylactic acyclovir for 6 months: a 17-year-old boy had recurrent cutaneous lesions as well as lesions in the oral cavity and lips. Positive serology for herpes simplex virus and histopathological examination confirmed the diagnosis.